2021
DOI: 10.1002/pbc.29110
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics prediction for MYCN amplification in neuroblastoma: A hypothesis generating study

Abstract: Background: MYCN amplification represents a powerful prognostic factor in neuroblastoma (NB) and may occasionally account for intratumoral heterogeneity. Radiomics is an emerging field of advanced image analysis that aims to extract a large number of quantitative features from standard radiological images, providing valuable clinical information.Procedure: In this retrospective study, we aimed to create a radiogenomics model by correlating computed tomography (CT) radiomics analysis with MYCN status. NB lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Previous studies have reported radiomics potential role to predict molecular biomarkers in neuroblastoma, including MYCN in neuroblastoma by CT-based radiomics signature [ 8 , 25 ], tumor-associated macrophages by contrast-enhanced CT [ 26 ]. Moreover, some studies demonstrated that combining radiomics features with clinical characteristics can provide incremental predictive value for gene mutant status and expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported radiomics potential role to predict molecular biomarkers in neuroblastoma, including MYCN in neuroblastoma by CT-based radiomics signature [ 8 , 25 ], tumor-associated macrophages by contrast-enhanced CT [ 26 ]. Moreover, some studies demonstrated that combining radiomics features with clinical characteristics can provide incremental predictive value for gene mutant status and expression.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies on radiomics in the pathological differentiation, molecular typing, and prediction of therapeutic effect of neuroblastomas. [9][10][11][12] These studies showed that radiomics has the potential for the accurate diagnosis of neuroblastomas. Therefore, radiomics is expected to provide a noninvasive evaluation method for risk stratification of neuroblastomas.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, medical images are not limited to providing subjective visual information. There have been some studies on radiomics in the pathological differentiation, molecular typing, and prediction of therapeutic effect of neuroblastomas 9–12 . These studies showed that radiomics has the potential for the accurate diagnosis of neuroblastomas.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on radiogenomics has greatly expanded in the past decade. Radiogenomics has been applied in various types of cancer, including lung cancer [70][71][72], breast cancer [73][74][75], genitourinary cancer [76][77][78], digestive system cancer [79][80][81], and brain cancer [82][83][84]. The comprehensive analysis method of radiogenomics can be used to diagnose and predict patient outcomes such as recurrence, metastasis, and survival of patients with cancer; predict the tumour microenvironment; identify potential molecular biomarkers and targets for clinical diagnosis and treatment; and establish a molecular typing system of variable cancers.…”
Section: Current Applications Of Radiogenomics In Cancermentioning
confidence: 99%